Prognostic role of liver X receptor‐alpha in resected stage II and III non‐small‐cell lung cancer. (25th July 2016) - Melloni, Giulio; Muriana, Piergiorgio; Bandiera, Alessandro; Fontana, Raffaella; Maggioni, Daniela; Russo, Vincenzo; Doglioni, Claudio; Zannini, Piero
Abstract: Introduction: In the search of new therapeutical strategies against non‐small‐cell lung cancer (NSCLC), the identification of new prognostic factors is crucial. Objectives: In this study, we analyzed the prognostic value of the liver X receptor‐alpha (LXR‐alpha), a nuclear receptor of a family of cholesterol derivatives called oxysterols, in patients with radically resected NSCLC. Methods: We retrospectively reviewed 140 stage II and III surgically treated NSCLC patients that were grouped by percentage of LXR‐alpha‐positive cells value above or below its median value. Tumor‐related survival was evaluated as primary end point. Results: The 5‐year overall and tumor‐related survival rates were 40% and 46%, respectively. The median percentage of LXR‐alpha‐positive cells was 20%. Patients with stage II NSCLC had higher LXR‐alpha values than those with stage III ( P  = .04). Univariate analysis demonstrated that both TNM stage and LXR‐alpha were significantly related to tumor‐related survival ( P  = .006 and P  = .004, respectively). The 5‐year tumor‐related survival rates in stage II and III NSCLC were 56% and 34%, respectively. The 5‐year tumor‐related survival rates in high and low LXR‐alpha value were 57% and 32%, respectively. The multivariate analysis showed that both TNM stage and LXR‐alpha were independent prognostic factors ( P  = .01 and P  = .007, respectively) with hazard ratio of 1.92 and 0.49, respectively. Conclusion: LXR‐alpha seems to be an independent prognostic factor indicating a better survival in completely resected stage II and III NSCLC patients.